2015
DOI: 10.5901/mjss.2015.v6n3s5p55
|View full text |Cite
|
Sign up to set email alerts
|

Regional Models on Managing the Public-Private Partnership Projects in Housing and Communal Complex

Abstract: Due to the crisis in Russia and the lack of sufficient financial resources, the problem of interaction between the state and the subjects of housing and communal services in the regions is rather urgent and requires an elaboration of an effective management model of public-private partnerships. The purpose of this article is to develop a management model of publicprivate partnership in the housing and utilities sector. Using econometric analysis methods, authors of this paper have analyzed regional projects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Consequently, ‗Development of Comfortable Urban Environment' priority project is connected with strategic municipal formation's development planning. Overall, it is obvious that a city is a sphere of conflict of various factors and interests [18][19][20]. The task of urban services and city authorities is to provide urban environment with opportunities for development and achievement of favourable conditions for citizens' life and activities.…”
Section: Practical Importancementioning
confidence: 99%
“…Consequently, ‗Development of Comfortable Urban Environment' priority project is connected with strategic municipal formation's development planning. Overall, it is obvious that a city is a sphere of conflict of various factors and interests [18][19][20]. The task of urban services and city authorities is to provide urban environment with opportunities for development and achievement of favourable conditions for citizens' life and activities.…”
Section: Practical Importancementioning
confidence: 99%
“…Among the factors identified are appropriate project identification and selection (Qiao et al, 2001;Węgrzyn, 2016) and transparent procurement process (Zhang, 2005a;Federal Republic of Nigeria (FRN), 2009;Gleave, 2012;Węgrzyn, 2016). In housing, studies have examined the objectives and success factors (UN-HABITAT, 2006; Abdul-Aziz and Jahn-Kassim, 2011), challenges (UN-HABITAT, 2006;Trankanont and Charoenngam, 2014) and the modus operandi of PPPs in housing (Aziz and Hanif, 2006;Abdul-Aziz, 2012;Filushina et al, 2015). Other studies are on the contexts in which PPPs have been applied (UN-HABITAT, 2006;Yuan et al, 2012) and their control mechanisms (Abdul- Aziz, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experience has shown that PPPs and their ability to supply private finance improves access, quality of service, operational efficiency, and tariff levels as dimensions of abovementioned sectors' performance (Marin, 2009). Such cooperation between the state and private entities aims to delegate the functions of the supply of water, gas, electricity, heat, utilities and maintenance of quality housing (Lydia & Olga, 2013), providing numerous benefits to both public and private partner (Filushina, Kolyhaeva, Minaev, Dobrynina & Merkuleva, 2015). At the same time, the transition from zero-based to program budgeting enables Serbian local governments to strictly monitor key performance indicators of state-owned utility companies and to compare their KPI's with KPI's of companies-partnerships between local government and private sector.…”
Section: Literature Reviewmentioning
confidence: 99%